Microplastic pollution in intertidal sediments along the coastline of China. (August 2020) - Wang, Qing; Shan, Encui; Zhang, Bin; Teng, Jia; Wu, Di; Yang, Xin; Zhang, Chen; Zhang, Wenjing; Sun, Xiyan; Zhao, Jianmin
Abstract: Research on microplastic (MP) pollution in the marine environment has received widespread attention in recent years. To assess the degree of MP contamination in the intertidal zone of China, the abundance, shape, particle size and composition of MPs in sediment were investigated in this study. Sediment samples were collected from 13 stations along the coast of China. The density separation method was employed to isolate MPs from sediment and the polymer types of the MPs were determined by Fourier transform infrared microspectroscopy. Our study demonstrated that MP pollution was widespread in the 13 intertidal stations. The average abundance of MPs was 309 ± 81 items/kg dry weight. Fiber accounted for 71.5% of the isolated MPs, and the particles of less than 500 μm accounted for the highest proportion (35.0%). A total of 12 polymers were identified; the main types were rayon (RY), polypropylene (PP), polyethylene terephthalate (PET) and polyethylene (PE). The shape and chemical composition of the MPs from the intertidal sediments of South and North China were different. In South China, MP fragments were more extensive, and PP was a more important component. In contrast, the intertidal sediments of North China contained more MP fibers with the majority being RY, indicating that the major source of MPs in the intertidal zone of North China may be domestic sewage. Additionally, the abundance of MPs in the intertidal sediments of the Pearl River and Jiulong River estuaries was higher than at other sites. A Spearman's correlation analysis showed that there was no correlation between MP abundance and sediment grain size or organic matter content. Our study highlights the ubiquitous distribution of MPs in the sediment along the coast of China and provides valuable information for risk assessment and source control of MP pollution in China's intertidal zone. Graphical abstract: Image 1 Highlights: Microplastic pollution level in intertidal sediment is relatively high. The shape and polymer type of MPs from the sediments of different regions are varied. The MP pollution level may be related with economic level and population. Our study provides valuable information for MP pollution risk assessment in China. Abstract : MP pollution level is relatively high in intertidal sediments of China with obviously different pollution characteristics between southern and northern areas.